Development of an automatic can crusher using programmable logic controller - N. A. A. Hadi; Lim Hui Yee; K. A. M. Annuar; Zulhilmi Bin Zaid; Z. A Ghani; M.F. Mohd Ab Halim; Amar Faiz Zainal Abidin; M. B. N. Shah (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The invention of a can crusher machine in this project is to reduce the wasted storage space occupied by the tremendous amount of use aluminium can at the commercial establishment like in the restaurant, cafeteria and bar. Basically, can crusher machine be operated in manual effort and time in the can crushing process. Shrinking the initial volume of empty used-aluminium cans down to 50% in more effective, faster and effortless way, as well as to develop a low-cost device that is suitable for the small-industry usage are mainly the objectives for the Automatic Can Crusher, where an automated process is executed in Automatic Can Crusher due to the automation in the modern world is inevitable and nominal to be used. The Automatic Can Crusher is run by a Programmable Logic Controller (PLC) with the aid of an inductive and capacitive sensor, where it is applied to detect whether the object is metal or non-metal. Overall, the system can be controlled manually through the push start and stop button as well as using the Human Machine Interface (HMI) using NB-Designer, for displaying the total of cans being crushed per day. The average result of empty can could shrink from 31% to 60 % of the original value, by using the attuned and compatible pressure for this system.